The Role of Bile Acid Excretion in Atherosclerotic Coronary Artery Disease - Gideon Charach; Alexander Rabinovich; Ori Argov; Moshe Weintraub; Pavel Rabinovich (International Journal of Vascular Medicine)
The impact of cholesterol and different classes of lipoproteins on the development of coronary artery disease (CAD) has been investigated in extensively during the past 50 years. The cholesterol metabolism is dependent on numerous factors, including dietary fat, fractional absorption of dietary cholesterol, tissue stores of cholesterol, endogenous cholesterol synthesis, and fecal bile excretion. Several studies showed significantly lower amounts of bile acid secretion in adult patients with CAD compared to non-CAD patients. Could it be that the inability to efficiently excrete bile acids may lead to CAD development?